The Potential of Pre-fermented Juice or Lactobacillus Inoculants to Improve the Fermentation Quality of Mixed Silage of Agro-Residue and Lucerne - Mu, Lin; Wang, Qinglan; Cao, Xin; Li, Hui; Zhang, Zhifei (Frontiers in Microbiology, 2022)
The objective of this study was to determine the effect of pre-fermented juice, Lactobacillus plantarum, and L. buchneri on chemical composition, fermentation, aerobic stability, dynamics of microbial community, and metabolic pathway of a mixture of lucerne, wheat bran (WB), and rice straw (RS). All mixtures were ensiled for 1, 3, 5, 7, 15, 30, and 45 d after treatment with uninoculated (control, C); L. plantarum (LP, 1 × 106 cfu/g of fresh weight (FW)); L. buchneri (LB, 1 × 106 cfu/g of FW); LP+LB (LPB, 1 × 106 cfu/g of FW of each inoculant); and pre-fermented juice (J; 2 × 106 cfu/g of FW). Four lactic acid bacteria (LAB) species from three genera were cultured from the pre-fermented juice, with W. cibaria being dominant. The inoculants increased lactic acid (LA), decreased pH, ammonia nitrogen (AN) compared to C silage at earlier stages of ensiling, and high dry matter (DM) and water soluble carbohydrate (WSC) content in inoculated silages. Adding LPB increased the abundance of L. plantarum, L. paralimentarius and L. nodensis, resulting in the lowest pH. Pre-fermented juice enriched W. cibaria, L. sakei, L. parabrevis, Pseudomonas putida, and Stenotrophomonas maltophilia, mainly enhanced accumulation of acetic acid (AA) and LA, and decreased pH, crude protein losses, AN, and hemicellulose contents. L. buchneri and L. brevis had a high abundance in LB-treated and J silages, respectively, inhibited undesirable bacteria, and improved aerobic stability with more than 16 d. In addition, the metabolic pathways changed with time and L. buchneri inoculants promoted global metabolism. In conclusion, inoculations altered bacterial succession and metabolic pathways in silage; LB and pre-fermented juice enhanced ensiling by promoting pH reductions, enhancing concentrations of LA and AA, and extending aerobic stability more than 16 d.